IDENTITY OF BLOOD GROUP FROM DENTAL PULP OF DECEASED HUMAN - B. KARTHIKA; M. ELUMALAI (International Journal of Pharma and Bio Sciences, 2013)
Forensic science has many maxims, perhaps the best known of which is that every contact leaves its trace (Locard principle). Forensic identification is to identify the deceased individual and the culprit in medicolegal cases. The blood group once it formed in an individual it can’t be changed in their life time and dental pulp is protected by the surrounding calcified structures namely enamel and dentin, so blood group and dental pulp use has its own significance in identity. This review discusses about the Identity of Blood groups from dental pulp of deceased human.